Termination of second messenger signaling in olfaction. - Boekhoff, I (1992)
By using isolated rat olfactory cilia and a fast kinetics methodology, it has been demonstrated that odorant-induced second messenger signaling in the millisecond time range is terminated via phosphorylation reactions catalyzed by specific protein kinases. The cyclic adenosine nucleotide pathway is turned off by kinase A activity, whereas the inositol trisphosphate cascade is terminated by kinase C. The data support the concept that desensitization of odorant responses involves phosphorylation of key elements in the transduction cascade.